MESSIANISM IN F. GORENSHTEIN'S NOVEL "PSALM" - Petrukhina Tatiana (Bright Mind Publishing, 2026)
The article analyzes the messianic theme in F. Gorenshtein’s novel Psalm (1975) within the context of the artistic and philosophical-religious explorations of literature in the second half of the twentieth century. The novel is examined as a polemical and non-canonical interpretation of the biblical narrative and the figure of the Antichrist. Particular attention is given to comparing Gorenshtein’s messianic concept with other national literary models (in particular, W. Hamdam’s novel Rebellion and Submission), as well as to analyzing the image of the Antichrist as the savior of the oppressed. The article concludes that Psalm is a synthetic work, combining features of a literary text, spiritual reading, and theological treatise.
Keywords: Messianism, eschatology, Antichrist, biblical narrative, spiritual dystopia, post-apocalypse, F. Gorenshtein, novel Psalm.